The Role Of Ice Breaking On Student Enthusiasm In Learning Islamic Religious Education - Nora Afnita; Martin Kustati; Rezki Amelia; Firda Khairati Amris; Farida Ariani (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2025)
Islamic Religious Education (PAI) learning is often faced with the challenge of low student enthusiasm, which has an impact on the lack of active participation and understanding of the material. One of the efforts to overcome this problem is by applying ice breaking as a fun and interactive learning strategy. This study aims to determine the effect of using ice breaking on students' learning enthusiasm in PAI learning. The approach used was quantitative with a quasi experimental design, with a sample of 40, namely the experimental group that received treatment and the control group that did not receive treatment. Data were collected through questionnaires, then statistically analyzed using t-test. The results showed that there was a significant difference between the learning spirit of students who were given ice breaking and those who were not. Students in the experimental group showed increased motivation, engagement, and higher enthusiasm during the learning process. in this finding, the use of ice breaking can be an effective strategy in creating a more interesting learning atmosphere for PAI. These results serve as a reference for teachers in integrating more creative approaches to build students' learning enthusiasm in a sustainable manner.